2021
DOI: 10.3390/nu13093056
|View full text |Cite
|
Sign up to set email alerts
|

Low Iodine Intake May Decrease Women’s Fecundity: A Population-Based Cross-Sectional Study

Abstract: Salt iodization is one of the most cost-effective strategies to eliminate iodine deficiency disorders (IDD). However, China’s dismantling of salt monopoly has reduced the availability of iodized salt in the susceptible population in pregnancy, which might cause IDD and have adverse health effects on both themselves and their offspring. The aim of our study was therefore to explore the association between IDD and women’s reproductive health. This is a population-based cross-sectional study conducted in 2018 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…However, an important research gap is that none of these studies evaluated thyroid autoimmunity or thyroid function, which may mediate the link between iodine intake and pregnancy rate. Although these previous studies [ 14 , 15 ] suggest a lower pregnancy rate in women with lower iodine intake, it is unknown whether high iodine intake is associated with a lower natural pregnancy rate.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, an important research gap is that none of these studies evaluated thyroid autoimmunity or thyroid function, which may mediate the link between iodine intake and pregnancy rate. Although these previous studies [ 14 , 15 ] suggest a lower pregnancy rate in women with lower iodine intake, it is unknown whether high iodine intake is associated with a lower natural pregnancy rate.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, high and low iodine intake may be associated with a decreased probability of conception through altered thyroid function and autoimmunity. A population-based cross-sectional study targeting pregnant women in China found that women with iodine deficiency (i.e., urinary iodine concentration < 150 µg/L) were more likely to report a time to pregnancy of longer than 13 months [ 14 ]. The longer time to pregnancy and lower probability of conception among women with lower iodine intake remained similar when the analysis was limited to women who conceived naturally [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations